Analisis Bioekonomi Perikanan Tuna Sirip Kuning (Thunnus albacares) di Pelabuhan Benoa, Bali - Najib, Nu'man; Susanjaya, I Gede Arya; Candra Negara, I Nyoman Suprihanta; Safitri, Diah Ayu; Negara, I Ketut Wija (Journal of Marine Research and Technology, 2022)
The fisheries sector survived economic, financial, and monetary crises. Tuna fisheries currently face several challenges: decreased productivity, smaller size, and fishing areas that tend to go to the high seas. This study aimed to analyze the biological and economic aspects of yellowfin tuna fishery resources in the landing area of ??Benoa Harbor, Bali. Data is taken from PSDKP, Benoa-Bali, in the form of a time series from 2015 to 2019, which includes information on ship departures, data on fishing or production results, data on efforts, and data on fish species. The data analysis used the Gordon Schaefer model approach to calculate the CPUE, MSY, MEY, and OAE capture effort. The average CPUE value for yellowfin tuna fisheries for 2015-2019 is around 13.0 tons/gear. In MEY conditions, production (h) is 5.593 tons with an effort (E) of 1.082 trips per year. In MSY conditions, production (h) is 5.754 tons per year, and effort (E) is 1.300 trips per year. In OAE conditions, production (h) is 3.207 tons per year, and effort (E) is 2.165 trips per year. The gain obtained in the MEY condition has a more excellent value than in the MSY condition. MEY's profit earned (?) Rp327.101.497.889 per year, and MSY's (?) Rp313.880.136.037 per year.